(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
The proposition of the constitution of the self as starting from the intersubjective relationship that emerges from the recognition of the other, presents the problem of the ontological foundation of the self. On one hand, the self cannot exist in isolation, but on the other, making its constitution subordinate to the relation with the other can debilitate the self as it is made dependent, for its constitution, on something different from the self. If the constitution of the self is dependent on the intersubjective relation the question of its origin arises: What are those who enter a relation before relating? If the self only recognizes itself recognizing another, what is it that it recognizes? These questions are directed towards the search for an ontological or metaphysical foundation for the study of phenomenological anthropology. The self cannot depend on the other, and this one, in turn, on the self. Paul Ricoeur’s philosophical anthropology, with its emphasis on the corporeal and historical nature of man, and its dialogue with Aristotle, offers answers to these questions. Ricoeur studies man from his inner life (beginning with his freedom) but does not forget that which makes it possible for a human being to recognize and to be recognized.